RELATIONSHIPS BETWEEN LIPID AND IMMUNE DISORDERS AT VARIOUS STAGES OF DEVELOPING EXPERIMENTAL DYSLIPIDEMIA - E. G. Lobanova; Yu. K. Karaman (Медицинская иммунология, 2014)
Abstract. It was found that development of lipid disorders in rats is accompanied by increased levels  of  tumor  necrosis  factor  alpha  (TNFα)  in  blood  and  liver,  decreased  cytokine  regulation  index,  thus  suggesting  arising  inflammatory  reaction  at  the  organ  and  systemic  levels,  exhaustion  of  functional  reserve  and  diminished  response of immunocompetent cells. Intensity of TNFα secretion depends on the duration of emerging  alimentary  dyslipidemia  in  rats,  i.e.,  maximal  amounts  of  TNFα  in  blood  and  liver  were  detected  at  day  30  of  evolving  dyslipidemia.  At  90th  and  180th  day  after  starting  the  alimentary  load,  a  gradual  inhibition  of  cytokineproducing  ability  by  immune  cells  is  observed.  In  the  course  of  evolving  alimentary  dyslipidemia,  the  patterns  of intra-and intersystemic interactions are altered towards increased correlations between lipid transport   and  immune  markers,  as  well  as  higher  intercorrelations  between  the  parameters  of  blood  lipid  metabolism  and  proinflammatory  cytokine  levels  in  the  liver.  (Med.  Immunol.,  2011,  vol.  13,  N  1,  pp  61-66)